The context of cognition: emerging perspectives - Federmeier, Kara D; Sahakyan, Lili (Psychology of learning and motivation, 2021)
The Context of Cognition: Emerging Perspectives, Volume 75 in the Psychology of Learning and Motivation series, features empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditioning, to complex learning and problem-solving.